Study of the Photosynthesis Response during the Gradual Lack of Water for 14 Olea europaea L. subsp europaea Cultivars and Their Adaptation to Climate Change - Genoveva Carmen Martos de la Fuente; Benjamín Viñegla; Elena Illana Rico; Ana Maria Fernández Ocaña (Plants, 2023)
Understanding the tolerance of plants to drought and their gradual response to lack of water is a multifaceted challenge that requires a combination of scientific research and technological innovation. Selecting naturally drought-tolerant plants and knowing their response to photosynthesis in a wide range of water availability opens a door to making decisions about the suitability of different cultivars to be implanted in specific geographical areas, based on their tolerance to drought and light absorption capacity. In this work, photosynthesis–light curves were carried out using a LiCor LI-6800 IRGA device, applying increasing light intensities to plants of 14 olive cultivars, either under control conditions (no water stress) or subject to moderate and severe water deficits. The plants were grown in a culture chamber under controlled conditions for photoperiod, air humidity, temperature, and carbon dioxide concentration. For each cultivar, the electronic transference ratio (ETR) in response to light was also obtained. Different equations were used to fit experimental data allowing us to calculate, with a regression coefficient above 0.95, different photosynthetic parameters such as the maximum photosynthetic capacity, the photosynthetic efficiency, the number of electrons or the number of photons to assimilate a molecule of CO2, and the effect of the lack of water on these parameters. This work represents the first contribution of the response to photosynthesis of many olive cultivars subjected to moderate and severe drought conditions. The parameters described, and the results provided, pave the road for subsequent work related to plant physiology and other areas of science and technology, and allow us to objectively compare the tolerance to water stress in these fourteen olive cultivars.